High-performance asymmetric pseudocapacitor cell based on cobalt hydroxide/graphene and polypyrrole/graphene electrodes - Cai, Xiaoyi (2016)
Cobalt hydroxide nanowires network grown on nitrogen modified microwave exfoliated graphite oxide (NMEG) with a specific capacitance of 610 F/g is successfully synthesized by a chemical precipitation method. Asymmetric-type pseudocapacitors are fabricated with Co(OH)2/NMEG and polypyrrole (PPy)/rG-O applied as positive and negative electrodes respectively. The electrochemical properties of the electrodes in three electrode and two electrode systems are systematically investigated in 1 M KOH electrolyte. Various supercapacitor devices, such as rG-O//Co(OH)2/NMEG, NG//NG, rG-O//rG-O, and PPy/rG-O//PPy/rG-O are assembled with electrochemical performance evaluated by cyclic voltammetry and galvanostatic charge/discharge measurements. The Co(OH)2/NMEG//PPy/rG-O asymmetric supercapacitor cells can achieve a high cell voltage of 1.6 V and an energy density up to 24.9 Wh/kg with an active materials loading of ∼5 mg/cm2, significantly higher than that of rG-O//Co(OH)2/NMEG (19.3 Wh/kg), NG//NG (16.4 Wh/kg), rG-O//rG-O (15.3 Wh/kg) and PPy/rG-O//PPy/rG-O (9.4 Wh/kg) supercapacitor devices under the same measurement environment. The PPy/rG-O is a superior negative electrode to match cobalt/nickel oxides/hydroxides based positive electrodes for supercapacitor devices.